Peran Surveilans Kesehatan Matra dalam Upaya Penanganan Dampak Kebakaran Rumah di Wilayah Sumatera Selatan - Intan Kumalasari; Nyayu Meutia; Fatimah Azzahra; Nayla Tazkiah (Lembaga Pengembangan Kinerja Dosen, 2025)
Matra Health is a form of health service specifically designed to maintain and improve public health in dynamic, complex, and constantly changing environmental conditions. This service plays a very vital role, especially in facing and handling various types of disasters, both natural disasters such as earthquakes, floods, and landslides, as well as non-natural disasters such as residential fires. One form of non-natural disaster that often occurs in densely populated areas is residential fires. This is caused by various factors such as unsafe electrical installations, a lack of public awareness of the dangers of fire, and buildings that are not resistant to heat or fire. Residential fires not only cause physical damage to buildings and infrastructure, but also cause various health problems, ranging from burns, respiratory problems due to smoke exposure, to psychological trauma, especially in vulnerable groups such as children, the elderly, and pregnant women. In response to these conditions, a dimensional health intervention activity was carried out from June 23 to 26, 2025 in areas affected by the fires under the coordination of the South Sumatra Regional Crisis Center. This activity aims to reduce health risk factors that arise after the fires through a series of actions such as multi-sector health surveillance, public health education, and distribution of logistical assistance. The activity also includes conducting rapid assessments using the Rapid Health Assessment (RHA) method, providing education on fire impact prevention, and distributing supplementary food to vulnerable groups. The results of the activity showed a significant increase in public understanding of the dangers of fire and the importance of preparedness for its impacts. Furthermore, the need to strengthen cross-sectoral coordination, such as health, disaster management, and social sectors, in disaster management was identified. It is hoped that this activity can serve as a model for strengthening community-based emergency response systems.